ASPEK KEADILAN ATURAN PAJAK INDONESIA DALAM MENGATUR TRANSAKSI EKONOMI DIGITAL: RESPON ATAS INVESTIGASI USTR - Indrajaya Burnama (Scientax, 2022)
The growth of digital economy around the world is rapidly increasing. According to a study by Google, Temasek, Bain, and Statista, Indonesia should be the largest digital economic market in South East of Asia. Therefore, a lot of people and industry involved in the digital economy from overseas came to Indonesia. However they are not implementing the tax obligation at all, not only income tax but also value added tax. So, they raise injustice among people and industry involved with digital economy. Until the government released Minister of Finance Decree number 35 Year 2019, Act number 2 Year 2020 and Minister of Finance Decree number 48 Year 2020. However, the regulations were being investigated by United States Trades Representative (USTR). This research discusses implementation of the principle of justice in several tax regulations that regulate digital economic activity as well as current example such as France, Australia and Singapore. This research uses a descriptive qualitative approach. The purpose of this research is to find out the application of the principle of justice in tax regulations related to the digital economy that has been carried out by the government.